To smooth or not to smooth : the impact of grants and remittances on the equilibrium real exchange rate in Jordan - Saadi-Sedik, Tahsin; Petri, Martin (IMF working paper ;, 2006)
This paper estimates the effect of grants and workers' remittances on Jordan's long-term equilibrium real exchange rate. We estimate an equilibrium path for the Jordanian real exchange rate using the Johansen cointegration methodology over the period 1964 to 2005. Controlling for other fundamentals, we find that both grants and workers' remittances appreciate the equilibrium real exchange rate in a statistically and economically significant way. We also find that assessing deviations of the actual real exchange rate from the estimated equilibrium real exchange rate is nontrivial because different smoothing methodologies and the nonsmoothed estimates give very different results.